Black hearts one platoon's descent into madness in Iraq's triangle of death - Frederick, Jim (Pan Books, 2010)
"This is an unflinching account of a small group of soldiers from the 101st Airborne Division's fabled 502nd Infantry Regiment--a unit known as "the Black Heart Brigade." Deployed in late 2005 to Iraq's so-called Triangle of Death, the Black Hearts found themselves in the country's most dangerous location at its most dangerous time. Hit by near-daily attacks, suffering a particularly heavy death toll, and enduring a chronic breakdown in leadership, members of one platoon descended, over their year-long tour of duty, into a tailspin of poor discipline, substance abuse, and brutality. Four 1st Platoon soldiers would perpetrate one of the most heinous war crimes of the Iraq War--the rape of a fourteen-year-old Iraqi girl and the cold-blooded execution of her family. Drawing on in-depth interviews with Black Heart soldiers, this is a timeless story about the fragility of character in the savage crucible of warfare."--From publisher description